The Role of Private Teachers in Enhancing Qur’an Literacy (Reading and Writing) of Grade V Students at SD Negeri 30 Baubau - Saiman, Ummi Salwah; Maudin, Maudin; Rusli, Rusli (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the role of private tutors in improving students’ ability in Al-Qur’an reading and writing (Qur’anic Literacy) among fifth-grade students at SDN 30 Baubau. The study employs a descriptive qualitative approach. The participants consisted of 23 fifth-grade students selected through total sampling, and 3 private tutors of Qur’anic Literacy chosen using purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The findings show that SDN 30 Baubau is located in a strategic area and accommodates students from diverse religious backgrounds. Students’ abilities in Qur’anic Literacy vary. Private tutors play an important role in improving these abilities by applying individualized approaches and varied teaching methods, which contribute to positive outcomes in both cognitive and affective aspects.